2020
DOI: 10.1039/d0mt00179a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane H+ pump at a crossroads of acidic and iron stresses in yeast-to-hypha transition

Abstract: Iron is an essential nutrient but is toxic in excess mainly under acidic conditions. Yeasts have emerged as low cost, highly efficient soil inoculants for decontamination of metal-polluted areas, harnessing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…To counteract this, the cell increased synthesis of amino acids (Aat2p/B02178g, Leu1p/B01364g, Gcv2p, Sam2p, Met6p/E12683g, Ilv5p/D03135g, Ses1p/F02629g, Gat1p/F17886g, and Shm1p/D22484g), molecular chaperones (Kar2p/E13706g, Sse1p/E13255g, and Ssa4p/D22352g), superoxide dismutase (Sod2p/B08921g), and the target aKGA, which are all known to play a role in scavenging ROS. The proposed mechanism is consistent with findings by Cogo et al ( 2020 ), showing that acidification of external pH is accompanied by enhanced H + efflux through the operation of plasma membrane H + -ATPase Pma1p (B22066g). Transportation of carboxylic acids exploits this preformed membrane H + gradient.…”
Section: External Stress Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…To counteract this, the cell increased synthesis of amino acids (Aat2p/B02178g, Leu1p/B01364g, Gcv2p, Sam2p, Met6p/E12683g, Ilv5p/D03135g, Ses1p/F02629g, Gat1p/F17886g, and Shm1p/D22484g), molecular chaperones (Kar2p/E13706g, Sse1p/E13255g, and Ssa4p/D22352g), superoxide dismutase (Sod2p/B08921g), and the target aKGA, which are all known to play a role in scavenging ROS. The proposed mechanism is consistent with findings by Cogo et al ( 2020 ), showing that acidification of external pH is accompanied by enhanced H + efflux through the operation of plasma membrane H + -ATPase Pma1p (B22066g). Transportation of carboxylic acids exploits this preformed membrane H + gradient.…”
Section: External Stress Factorssupporting
confidence: 91%
“…It is known that even under extreme acidic environmental conditions (pH 3.0), the intracellular pH of a eukaryotic cell can still be maintained near neutrality (pH ~ 6.8), but the metabolic effort required to maintain the homeostasis is significant (Madshus 1988 ). It was shown that under pH 3.0, the abundance and activity of plasma membrane H + -ATPase Pma1p (B22066g) is significantly higher than at pH 4.5 or 6.0 (when it pumps H + ions inwardly) (Cogo et al 2020 ). Pma1 which generates the proton gradient and drives the active transport of nutrients by H + -symport is the most abundant protein in the yeast plasma membrane (Ferreira et al 2001 ).…”
Section: External Stress Factorsmentioning
confidence: 99%
See 1 more Smart Citation